2007
DOI: 10.1563/0.845.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anesthetics Containing Lidocaine and Epinephrine on Cardiovascular Changes During Dental Implant Surgery

Abstract: The purpose of this study was to evaluate cardiovascular changes during dental implant surgery using 2% lidocaine with 1:80 000 epinephrine. Eleven normotensive subjects, ranging from 18 to 56 years, were selected to undergo dental implant surgery in the jaw. They were monitored in the pre-, intra-, and postsurgical periods by continuous noninvasive automatic arterial pressure and cardiac frequency measurements taken every 2 minutes. Parameter scores were obtained for the following phases: P1, 15 minutes durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
2
5
0
3
Order By: Relevance
“…In the current study, the measured parameters returned back to baseline reading 10 minutes after the completion of tooth extraction as the stress and fear induced by surgical procedure, were terminated 16 . Furthermore, In the current study, we found that diastolic blood pressure increased at 10 minutes post local anaesthetics injection in a similar way to systolic blood pressure but to less extent, this finding is in agreement with previous studies 5, 20,21 . There was a significant increase of heart rate during extraction in both groups as compared to their corresponding baseline values; However, the differences between the normotensive and hypertensive were not significant.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, the measured parameters returned back to baseline reading 10 minutes after the completion of tooth extraction as the stress and fear induced by surgical procedure, were terminated 16 . Furthermore, In the current study, we found that diastolic blood pressure increased at 10 minutes post local anaesthetics injection in a similar way to systolic blood pressure but to less extent, this finding is in agreement with previous studies 5, 20,21 . There was a significant increase of heart rate during extraction in both groups as compared to their corresponding baseline values; However, the differences between the normotensive and hypertensive were not significant.…”
Section: Discussionsupporting
confidence: 94%
“…survey on the effect of anesthetics containing lidocaine and epinephrine on cardiovascular changes during dental implant surgery, blood pressure was evaluated using the automated noninvasive oscillometric technique during ten steps; the results showed no significant difference in blood pressure and heart rate variability,[7] which is not in accordance to the findings achieved in this research.…”
Section: Discussionmentioning
confidence: 68%
“…In spite of the effect of local anesthetics on vital signs, their accurate application is able to dramatically reduce stress. [7]…”
Section: Introductionmentioning
confidence: 99%
“…23,24,25 Anxiety and fear of endodontic treatment were reported by a large number of patients during this study. These emotions can generate significant autonomic changes and determine physiological changes related to sympathetic nervous system activity, expressed as pallor, sweating palms, t rembli ng, com mun icat ion di fficult ies a nd tachycardia.…”
mentioning
confidence: 68%